Integrated Transport Policy - Planning Commission (Planning Commission Government of India, 2001)
The Integrated Transport Policy of India, developed by the Planning Commission, provides a strategic framework to modernize and expand the nation’s transport infrastructure across railways, roads, ports, civil aviation, and urban transport. Despite significant growth over the past five decades, the sector faces critical challenges, including capacity shortages, poor road quality, and inadequate rural connectivity. The policy emphasizes modal efficiency, regional integration, sustainable practices, and enhanced private sector participation. Key strategies include augmenting rail and road capacities, upgrading airports and ports, developing mass rapid transit systems, and integrating land use with transport planning. By promoting intermodal coordination, technological modernization, and phased infrastructure investment, the policy aims to create an efficient, safe, and sustainable transport system that supports economic growth and equitable access across India.
Planning Commission Government of India October 2001
Keywords: Integrated Transport Policy; Railways; Roads; Urban Transport; Ports; Civil Aviation; Infrastructure Development; Capacity Augmentation; Rural Connectivity; Private Sector Engagement; Sustainable Transport; Intermodal Efficiency